Designing a Macro-VBA Excel-based Kit List Printing Application for the Supporting Department of PT XYZ - Pribadi, Marius; Putrianto, Novenda Kartika; Purnomo, Purnomo (Teknik Industri Universitas Ma Chung, 2023)
The recording of raw material orders in PT.XYZ must be done through the embedded ERP system in the company, Microsoft Dynamics GP. However, the system is not perfect as it is not suitable for workers who follow traditional practices. To avoid losing goods, PT XYZ has started implementing kit recording, but a shortage of workers who enter KIT data can lead to human error. To overcome this, PT XYZ can automate the printing of KIT using VBA in Microsoft Excel. VBA allows applications to work more efficiently by easily manipulating object models. Excel macros support VBA programming and enhance the flexibility of the programming language. A well-organized VBA Excel application can produce a KIT list by pulling data from the production order sheet attached to the bus chassis as it moves on the production line. Once the specifications for a bus body to be produced are obtained, the user can edit and click one button to get the KIT that is suitable for that bus. Therefore, VBA in Excel can help PT XYZ improve the recording of raw material orders and reduce human errors that can cause financial losses.